Neurological complications in AIDS patients: The 1-year retrospective study in Chiang Mai University, Thailand - Subsai K. (2014)
The first case of AIDS patient in the northern part of Thailand was reported in 1987 (Vithayasai et al., 1996), marking the outbreak of an epidemic. In our experience, the neurological involvement in AIDS patients seems to have changed in pattern and incidence during the last 8 years. We have conducted a retrospective study to review the incidence of AIDS-defining diseases in the patients admitted to Chiang Mai University Hospital, Thailand during the period September 2001 to August 2002. There were 155 AIDS patients admitted during this specified period, 118 of which were male and 37 female, aged between 16 and 60. The incidence of neurological complications was 50.3 per 100 person-years, in which central nervous system involvement account for 46.5 per 100 person-years and peripheral nervous system involvement account for 3.8 per 100 person-years. The incidence of cryptococcal meningitis appeared to be decreasing since 1994 whereas the incidence of cerebral toxoplasmosis appeared to be increasing. The incidence of cryptococcal meningitis, cerebral toxoplasmosis and cytomegalovirus (CMV) infection was 18.0, 14.8 and 7.0 per 100 person-years, respectively. Other common non-neurological AIDS-defining illnesses in northern Thailand include pulmonary tuberculosis (15.4 per 100 person-years), extrapulmonary tuberculosis (9.6 per 100 person-years), and disseminated penicilliosis (12.2 per 100 person-years). In this way and summarizing, in northern Thailand, the three most common neurological involvements before the era of highly active anti-retroviral therapy are cryptococcal meningitis, cerebral toxoplasmosis and CMV infection. The incidence of cryptococcal meningitis appeared to be decreasing whereas the incidence of cerebral toxoplasmosis seemed to be increasing.